Finnish Case of Basic Education for All – With Quality Learning Outcomes - Kuusilehto-Awale, Lea; Lahtero, Tapio (Journal of Education and Research, 2014)
This article views behind the success of the Finnish basic education in the PISA assessments in the years 2000, 2003, 2006 and 2009. Success is here defined not only as excellent learning outcomes in reading literacy, mathematics and science, but also as a high level of educational equity and equality. The achieved outcomes are attributable to several factors, of which this article addresses especially the basic education reform of 1972-1977 and the university based teacher education leading to a master’s degree. Additional attention is paid to the autonomy of the municipalities (counties), schools and teachers in building and implementing the curricula, on the respect for learning and teachers in the Finnish society, and on the role of the Finnish evaluation system in supporting the student’s learning. Developing education is a long range effort continuing across election terms, as education is understood to be a cornerstone for the development of the society. This fact justifies our describing some of the Finnish national background bases for the comprehensive basic education system, where all students study in the same group. DOI: http://dx.doi.org/10.3126/jer.v4i1.9619 Journal of Education and Research, March 2014, Vol. 4, No. 1, pp. 1-18